National Human Rights Institutions and ASEAN Intergovernmental Human Rights Commission (AICHR): Are They Complementary? - Hooi, Khoo Ying (Malaysian Journal of International Relations, 2017)
The adoption of the Association of Southeast Asian Nations (ASEAN) Charter in 2008 and the establishment of the ASEAN Intergovernmental Human Rights Commission (AICHR) in 2010 have pushed ASEAN to be more responsive to human rights commitments in the region. In view of the regional developments and the increase of transboundary concerns, the six government-established national human rights institutions (NHRIs) in the Philippines, Indonesia, Malaysia, Thailand, Timor-Leste and Myanmar formed the Southeast Asia National Human Rights Forum (SEANF) in 2009 to organise itself as a regional mechanism for human rights promotion and protection in ASEAN. So far, the relationship between the ASEAN Intergovernmental Commission of Human Rights (AICHR) and the SEANF has not been progressing. The purpose of this paper is to examine the potential role of SEANF in addressing human rights issues with the existing regional human rights mechanism, the AICHR.